The Influence of Job Satisfaction, Work Environment, Individual Characteristics and Compensation toward Job Stress and Employee Performance - Riyadi, Slamet (International Review of Management and Marketing, 2019)
This study aims to reveal and to analyze the influence of Job Satisfaction, Work Environment, Individual Characteristics andCompensation toward Job Stress and Employee Performance of Minerals & Metals Manufacturing Sector in East Kalimantan. The sample is drawn from members of 120 Minerals & Metals Manufacturing Sector companies which represented by 1 employee whose position as a manager. Data processing uses SEM (Structural Equation Modeling) which obtained 7 acceptable hypotheses and 2 rejected hypotheses.7 accepted hypotheses are: 1). Job satisfaction significantly and negatively relates to job stress. 2).work environment significantly and negatively relatesto job stress. 3) Individual characteristic significantly and negatively relates to job stress. 4). Compensation significantly and negatively relates to job stress. 5). Job satisfaction significantly and positivelyinfluencesemployee performance. 6). Compensation positively and significantlyinfluencesthe employee performance. 7). Job stress negatively and significantly influences the employee performance. Furthermore, the two rejected hypotheses are: 1). the work environment is not a significant influence on employee performance. 2) Individual characteristics do not significantly affect the employee performance. Keywords: Job Satisfaction, Work Environment, Individual Characteristics, Compensation, Job Stress and Employee Performance. JEL Classifications: I12, J33, M54 DOI: https://doi.org/10.32479/irmm.6920